Synergistic Effect of Newly Introduced Root Canal Medicaments; Ozonated Olive Oil and Chitosan Nanoparticles, Against Persistent Endodontic Pathogens - Elshinawy, Mohamed I.; Al-Madboly, Lamiaa A.; Ghoneim, Walaa M.; El-Deeb, Nehal M. (Frontiers in Microbiology, 2018)
This study was conducted to investigate the antimicrobial-biofilm activity of chitosan (Ch-NPs), silver nanoparticles (Ag-NPs), ozonated olive oil (O3-oil) either separately or combined together against endodontic pathogens. While testing the antimicrobial activity, Ch-NPs showed the least minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values exerting 8-fold higher bactericidal activity than O3-oil against both Enterococcus faecalis and Streptococcus mutans as well as 4-fold higher fungicidal activity against C. albicans. Antimicrobial synergy test revealed synergism between O3-oil and Ch-NPs against the test pathogens (FIC index ≤0.5). Ch-NPs was superior at inhibiting immature single and mixed-species biofilm formations by 97 and 94%, respectively. Both of O3-oil and Ch-NPs had a complete anti-fibroblast adherent effect. The safety pattern results showed that O3-oil was the safest compound, followed by Ch-NPs. The double combination of Ch-NPs and O3-oil reduced the mature viable biofilm on premolars ex vivo model by 6-log reductions, with a fast kill rate, indicating potential use in treating root canals. Therefore, the double combination has the potential to eradicate mature mixed-species biofilms and hence it is potent, novel and safe.